FRAGMENTATION OF TIME IN A PAIXÃO SEGUNDO G.H. AND IN GRANDE SERTÃO: VEREDAS (Muitas Vozes, 2021)
It can be found, in the midst of modern literature, works which made the theme of temporality the matter of literary creation. Based on this perspective, the objective is to show the aspect of temporal fragmentation in the construction of A paixão segundo G.H., by Clarice Lispector, and Grande sertão: veredas, by Guimarães Rosa. By comparing these two novels, it will be possible to show out how the construction of a temporarily fragmented writing allows the emergence of a literature that makes the notion of reality and humanity be questionable and, thereby, it changes the relationship between form, time and language.